2002
DOI: 10.1080/15226510208500090
|View full text |Cite
|
Sign up to set email alerts
|

Biotransfer Possibilities of Selenium from Plants Used in Phytoremediation

Abstract: We are investigating the biotransfer of accumulated Se by the plant in several phytoremediation systems. In study I, we evaluated the biotransfer of Se from Indian mustard, a Brassica species, to the insect-cabbage looper (Trichoplusia ni); mortality, deterrence, and biomagnification of Se were examined. We determined that feeding behavior of food chain consumers was affected not only by the plant concentration of Se, but also by the mobility of the insects and choice of feed available. In study II, we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 22 publications
5
33
1
Order By: Relevance
“…The presence of Se in irrigation water increased plant resistance to the insect tested in this model system, which is in agreement with the data generated for Indian mustard (Ban˜uelos et al, 1999). This suggests that Se may enhance plant resistance to the beet armyworm, but the literature is too limited to allow definitive generalizations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The presence of Se in irrigation water increased plant resistance to the insect tested in this model system, which is in agreement with the data generated for Indian mustard (Ban˜uelos et al, 1999). This suggests that Se may enhance plant resistance to the beet armyworm, but the literature is too limited to allow definitive generalizations.…”
Section: Discussionsupporting
confidence: 89%
“…Possible biotransfer of Se from plants to insects may not only have consequences for the pest insects , but also for vertebrates and invertebrates that feed on insect herbivores (Wu et al, 1994). Unfortunately, data on effectiveness of cultivated and uncultivated plants in Se accumulation and as hosts for pest insects are minimal (Ban˜uelos et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There was one exception; selenium, indicative of coal spoil, was higher than county and state averages and in the higher concentration range of common US soils. Also noted, drip lines were significantly lower in selenium than reference soils (soils lacking tree plantings or soil preparation [63] and it has been suggested that 4 ppm of selenium in plants is the tolerance limit for animals and levels above 5 ppm could be a concern [64]. Although we did not test levels in chestnut seed, we found floral tissue to average 7.3 ppm, which may merit closer inspection of the developing chestnut seed on legacy sites.…”
Section: Discussioncontrasting
confidence: 40%
“…These results were not unexpected. Studies using insect herbivores (Hogan and Cole, 1988;Trumble et al, 1998;Ban˜uelos et al, 1999;Vickerman and Trumble, 1999), or insect predators (Vickerman and Trumble, 2003) also found reduced survivorship and/or delayed development. Our results show that Se contamination similarly affects insect detritivores.…”
Section: Discussionmentioning
confidence: 99%
“…In aquatic systems, insects feeding on algae are known to bioaccumulate Se (Malchow et al, 1995;Thomas et al, 1999) and are important primary consumers and prey in systems where bioaccumulation has been demonstrated (Lemly, 1993). In terrestrial systems, transfer of Se from plants to herbivores has been documented (Trumble et al, 1998;Ban˜uelos et al, 1999;Vickerman et al, 2002a, and references therein), as has the transfer from an herbivore to an insect predator (Vickerman and Trumble, 2003).…”
Section: Introductionmentioning
confidence: 99%